Penanganan Dampak Kemacetan Lalu Lintas Pada Pembangunan Kawasan Industri Baru - Muhajirin Muhajirin (Jurnal Jalan-Jembatan, 2005)
In any new housing and settlement area it is necessary to carry out environmental assesment based on Environmental Impact Analysis Study (EIA) which is stimulated in Government Ordinance (PP) number 27, 1999. In handling the traffic jam impact in sample city of Serang. It was stated that traffic jam level in east road before peak hour, between 07.30 – 08.00 has reached the amount of 1286 vehicles/hour. In the evening, between 16.30 -17.00 it has reached 1699 vehicles/hour. Reffering the noise level exceeded maximum required that is 51.0 dBA (max = 60 dBA), hence it is categorized as negative not important. This condition can cause damage to infrastructure especialy road due to vechicles passing in carrying-out contruction tools and material, therefore it is stated as negative-important.